Prevalence of prediabetes in apparently healthy population of Tehsil Kangra and adjoining areas - Bisht, Inderamohan; Dhanda, Saurabh; Chauhan, Suman Kumari; Yadav, Rajinder; Yadav, Suman (International Journal Of Community Medicine And Public Health, 2018)
Background: More than 50% of the diabetes mellitus (DM) subjects in India remain unaware of their diabetic status. The aim of the study was to screen and identify apparently healthy individuals for impaired glucose tolerance in Tehsil Kangra and adjoining areas of Himachal Pradesh, India. Methods: Cross sectional study with 80 apparently healthy subjects in the age group of 30 to 70 years were taken. Anthropometric parameters viz. weight, height and waist circumference of subjects were measured. Whole blood sample was used for estimation of glycosylated hemoglobin (HbA1c) and serum sample for fasting blood sugar (FBS) and some lipid parameters. Results: The prevalence of prediabetes in apparently healthy population was found to be 25%. Additionally, a significant increase was observed in the FBS levels in prediabetics as compared to healthy subjects. However, no significant change was observed in the mean body mass index (BMI), mean body surface area (BSA), waist to height ratio (WHtR) and lipid parameters between prediabetics and healthy subjects. Conclusions: The burden of prediabetes in apparently healthy subjects of Tehsil Kangra and adjoining areas was found to be 25% and this urgently calls for mass awareness and screening programmes to identify and overcome DM.